Links of Hydrogen Sulfide Content With Fluid Components and Physical Properties of Carbonate Gas Reservoirs: A Case Study of the Right Bank of Amu Darya, Turkmenistan - Cheng, Youyou; Feng, Zhao; Guo, Chunqiu; Chen, Pengyu; Tan, Chengqian; Shi, Haidong; Luo, Xiang (Frontiers in Earth Science, 2022)
Hydrogen sulfide (H2S) in carbonate gas reservoirs shows strong relevance with the natural gas components, and has an obvious impact on reservoir types and their petrophysical properties. In this work, core and fluid samples were collected from the Right Bank of Amu Darya reservoirs, Turkmenistan. Then, fluid composition analysis and flash evaporation experiments were performed to investigate the components of reservoir fluid. Petrophysical properties, i.e. porosity and permeability, and micro-pore structures of cores were determined by permeameter-porosimeter and scanning electron microscope (SEM) analysis, respectively. Results in this work indicate that the H2S content shows obvious relevance to fluid components in carbonate gas reservoirs. With the increase of H2S content, the total heavy hydrocarbons and potential condensate content decrease, while the condensate density increases. In addition, at higher H2S content, larger pore and vug porosity was observed. However, in reservoirs with lower H2S content, the matrix pores are relatively tight and prone to develop with fractures. Furthermore, sulfate thermochemical reduction (TSR) is found to be the dominant contributor to high H2S content in carbonate reservoirs through material and thermodynamic condition analysis. The Gibbs free energy and normalized hydrocarbon content show that the consumption of heavy hydrocarbons generally increases with carbon numbers during TSR, but reaches a minimum at the components of C7 to C9. Finally, relationship between TSR and rock petrophysical properties were discussed, indicating that pore volume enlargement and the dissolution effect of acidic gases are the main mechanisms for TSR to improve carbonate reservoir property. Results in this study present comprehensive analyses on the links between H2S content and fluid components and petrophysical properties in carbonate gas reservoirs.